2010
DOI: 10.1111/j.1365-2400.2010.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of adult Pacific lamprey in near-field flow and fishway design experiments

Abstract: An experimental fishway was used to examine adult Pacific lamprey, Lampetra tridentata (Gairdner), behaviour in a series of attraction and passage-performance tests. Among all experiments, lamprey oriented to the fishway floor and walls and were attracted to both ambient and concentrated flow. When confronted with highvelocity areas (vertical-slot and submerged-orifice weirs), many lamprey failed to pass upstream. However, lamprey were able to find and take advantage of low-velocity refuges when they were prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…Furthermore, whilst peaks in lamprey visitation to both fishways on a given day were highest during high flow events, outside of release dates, markedly fewer lamprey visited the pool and weir fishway on a given day than the Denil fishway. These observations can be attributed to the pool and weir's low fishway discharge and the suboptimal, perpendicular orientation of the attraction flow in relation to the barrier; these factors have proved to be problematic for other fish species attempting to locate fishway entrances (Aarestrup et al, 2003;Bunt, 2001;Gowans et al, 1999;Keefer et al, 2011;Laine et al, 1998;Larinier et al, 2005). September to March, was never exceeded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, whilst peaks in lamprey visitation to both fishways on a given day were highest during high flow events, outside of release dates, markedly fewer lamprey visited the pool and weir fishway on a given day than the Denil fishway. These observations can be attributed to the pool and weir's low fishway discharge and the suboptimal, perpendicular orientation of the attraction flow in relation to the barrier; these factors have proved to be problematic for other fish species attempting to locate fishway entrances (Aarestrup et al, 2003;Bunt, 2001;Gowans et al, 1999;Keefer et al, 2011;Laine et al, 1998;Larinier et al, 2005). September to March, was never exceeded.…”
Section: Discussionmentioning
confidence: 99%
“…Only in recent years have these designs been evaluated, on site or in laboratories, for less economically important or 4 less well-understood taxa (e.g. Cypriniformes, Anguilliformes, Perciformes, Characiformes) (Bunt et al, 1999;Keefer et al, 2011;Laine et al, 1998;Lucas et al, 1999Lucas et al, , 2000Makrakis et al, 2011;Kemp, 2011a, 2011b;Thiem et al, 2012;White et al, 2011). Improved understanding of the behaviour and passage ability of a wider range of species is needed, through laboratory and field studies, if we are to move further towards effective multi-species fish passage provision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In similar sets of experiments, Keefer et al (2011) found that adult lamprey were able to find and use relatively low-velocity routes when given a choice between high (2.9-3 m/s) and lower velocity (0.1-1.2 m/s) treatments. used both an experimental flume and field observations to document adult Pacific lamprey behaviors in fishways at a large hydropower dam.…”
Section: Behavioral Responses To Barriersmentioning
confidence: 90%
“…Unlike teleost fishes (particularly salmonids), lampreys are relatively poor swimmers and use their oral disc to attach and rest in high velocity situations (e.g., Quintella et al 2004;, although climbing abilities differ among species (Moser et al 2011). Improvements to passage structures are now being implemented in some areas to improve lamprey passage efficiency (e.g., Keefer et al 2011;Moser et al 2011;see Chap. 5).…”
Section: Barriers To Passagementioning
confidence: 99%